Biofilm Formation of Escherichia coli on Hydrophobic Steel Surface Provided by LaserTexturing Investigation of modified surfaces to prevent biofilm formation - Arkan-Ozdemir, Simge; Cansever, Nurhan; Ilhan-Sungur, Esra (JOHNSON MATTHEY PUBL LTD CO, 2023)
Lozenge-patterned surfaces obtained with laser texturing can reduce the risk of infection by preventing or delaying biofilm formation of Escherichia coli. To investigate this aspect, the biofilm formation ability of E. coli on both lozengepatterned and untreated surfaces of 630 stainless steel coupons was examined over 48 h. Biofilm on the coupons was analysed for bacterial enumeration and total carbohydrates concentration and was observed using scanning electron microscopy (SEM). The surface modification by texturing caused a 6 h delay in the attachment of E. coli and an approximately 99% decrease in the number of adhered bacteria. However, it was determined that E. coli produced more extracellular polymeric substances (EPS) (p<0.01) to attach to the lozengepatterned surface and formed a multi-layered biofilm. In conclusion, lozenge-patterned surfaces can be applied to reduce bacterial count and induce a delay in attachment, but the increased amount of EPS limits its use.
Keywords: EXTRACELLULAR POLYMERIC SUBSTANCES; BACTERIAL ADHESION; STAPHYLOCOCCUS-AUREUS; POLYSACCHARIDE; EPIDERMIDIS; MECHANISMS; EXTRACTION; ATTACHMENT; RESISTANCE; CORROSION; Chemistry